Tax policy in the context strengthening the national security of Ukraine - Klymenko, Kateryna; Ukhnal, Nataliia; Semenyshena, Nataliia (Public Policy and Accounting, 2023)
In the article, the authors substantiated the need to reform and improve the efficiency of tax policy to ensure national financial and economic security. It has been determined that the main problems of tax policy, taking into account the introduction of martial law, hinder the development of entrepreneurial activity, lead to a decrease in production, a decrease in investment in the national economy, a reduction in incomes of the population, an increase in defense spending and state debt due to dependence on foreign aid and loans, which in general, it can lead to a decrease in the country's defense capability and security, in particular, its financial sovereignty. The importance of adopting the law of Ukraine "On Amendments to the Tax Code of Ukraine and other legislative acts of Ukraine on the implementation of the international standard for automatic exchange of information on financial accounts", part of the implementation of the BEPS plan (measures to counteract the erosion of the taxable base and the removal of profits from taxation), developed by organization of the OECD and aimed at ensuring that the competent authorities have access to this information in order to effectively identify undeclared income of tax residents outside the countries and control the correctness of declaring income and paying taxes, which in turn will contribute to the proper fulfillment by our state of international obligations on the exchange of information. for tax purposes provided for by the current double taxation conventions, the Convention on Mutual Administrative Assistance in Tax Matters, the CRS Multilateral Agreement and the implementation of the best international policies and practices in this area. The authors of the article also consider the importance of international cooperation to improve the efficiency of tax policy, in particular, in the area of concluding tax agreements and openness of tax registries. Gaining access to tax registries contributes to the fight against the shadow economy and crime, as it will allow you to control financial transactions and identify undeclared income. In particular, the conclusion of tax agreements between countries can reduce double taxation and stimulate the investment climate. It is revealed that undeclared economic activity, which is one of the forms of the shadow economy, and the lack of effective control over compliance with tax laws, leads to an increase in tax losses, which in turn affects the financial stability of the state. The importance of developing and implementing an effective tax administration system in the context of the National Revenue Strategy (which is one of the “structural beacons” declared in the Memorandum on Economic and Financial Policy with the IMF, which will avoid tax evasion, reduce the risks of financial instability and ensure stable growth in revenues) is noted. to the state budget It is noted that the successful implementation of the tax policy reform requires responsibility on the part of state bodies, society and business for the process of forming a tax culture, which will help raise the level of consciousness of citizens about the need to pay taxes and their importance for the development of the state.